Theories, practices, and challenges of teaching and learning Arabic as a modern language at the secondary stage in Dubai - Abu Ateyh, Nour Atta (Journal of Curriculum and Teaching Methodology, 2024)
Language serves as the cornerstone of communication and cultural development in any society. In Dubai’s schools, the teaching of Modern Foreign Languages (MFL), including Arabic, is emphasized at the secondary level, reflecting the UAE’s commitment to Arabic as a vital element of its identity. This study examines the integration of language teaching theories into the practice of teaching Arabic as an MFL and identifies the challenges faced by educators in Dubai. Despite the theoretical frameworks provided by the Ministry of Education, many Arabic MFL teachers lack awareness of these theories, relying instead on personal teaching practices. This research highlights three primary teaching approaches—audio-lingual, grammar-translation, and communicative—comparing their effectiveness and application in Arabic MFL classes. A qualitative methodology, including surveys and lesson observations, reveals a significant gap between theoretical knowledge and practical application among teachers. The study identifies several challenges, such as curriculum constraints, mixed student proficiency levels, and the dominance of English in Dubai, which hinder effective Arabic language instruction. The findings underscore the need for better theoretical grounding and innovative practices among teachers to enhance the learning experience. Recommendations for future research include exploring teachers’ perspectives on the most effective teaching methods and addressing the complexities of mixed-level classes to improve Arabic MFL education in Dubai. While this study has considered the importance of connecting theories to practices in teaching Arabic as a Modern Foreign Language (MFL) and the challenges faced by Arabic MFL teachers, there is still a need for further research. Future studies should investigate Arabic teachers’ opinions on the most effective methods for teaching Arabic as an MFL and explore the reasons why teachers might learn about these methods without implementing them in practice. Additionally, more research is needed on how to effectively teach mixed-level Arabic MFL classes and create an optimal learning environment in such settings.